Development a stacking pad design for enhancing the sensitivity of lateral flow immunoassay. Issue 1 (December 2018) - Tsai, Tsung-Ting; Huang, Tse-Hao; Chen, Chung-An; Ho, Natalie; Chou, Yi-Ju; Chen, Chien-Fu
Abstract Lateral flow immunoassays (LFIAs) have wide application in point-of-care testing, particularly in resource-poor settings. To achieve signal amplification in a gold nanoparticle-based lateral flow assay without an additional procedure or the need for complex fabrication, a new and simple method was developed for using a "stacking pad" configuration that adds an additional membrane between the conjugation pad and test pad to the conventional AuNP-based LFIA format. This design helps to accumulate the antibody and antigen on the stacking pad, hence extending the antigen/antibody binding interactions to enhance the test's detection sensitivity. With the enhanced lateral flow assay, as low as 1 ng/mL of Protein A and 15.5 ng/mL of C-reactive protein can be visualized with the naked eye. We also successfully applied the stacking pad system in the analysis of C-reactive protein in human serum and synovial fluid samples. These results suggest that this stacking pad LFIA can provide sensitive and on-site prognosis for detection in synovial fluid and serum samples in resource-limited settings.